2011
DOI: 10.1007/s13105-011-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of combining intermittent hypoxia and physical exercise in the treatment of obesity

Abstract: SummaryObesity is an important public health problem worldwide and is a major risk factor for a number of chronic diseases such as type 2 diabetes, adverse cardiovascular events and metabolic syndrome related features. Different treatments have been applied to tackle body fat accumulation and its associated clinical manifestations. Often, relevant weight loss is achieved during the first six months under different dietary treatments. From this point, a plateau is reached, and a gradual recovery of the lost wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
108
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 155 publications
5
108
1
1
Order By: Relevance
“…Thus, one of the mechanisms triggering inflammation has been associated with adipose tissue hypoxia [4] or increased oxygen tension [5], which affect a number of genes such as HIF-1a, MCP-1, IL-6, GLUT-1, ANGPTL-4 and PPAR-γ [6] that could be involved as a cause or as a consequence reaction to pathologically low or high oxygen conditions. Interestingly, as we hypothesized previously [3] and Kong et al have nicely demonstrated in their article [1], hypoxia is not only an ethological factor or a manifestation of disease, but also a therapeutic tool following different patterns (hypoxic exposure, hypoxic training, intermittent hypoxia under hyperbaric and normobaric conditions), which has been used for pre-acclimation in climbers, or to improve athletes performance as well as for heart, respiratory and nervous system diseases or to regulate body weight [7]. Thus, putative compensatory mechanisms and responses to hypoxia has been described for the respiratory system (hyperventilation, improvement in respiratory function and increase in lung diffusion capacity), in the cardiovascular system (increase in basal heart rate, peripheral vasodilation, normalization of blood pressure or cardiovascular protection), in cellular and metabolic phenomena (angiogenesis, insulin sensitivity enhancement, enzymatic activation or mitochondrial biogenesis), as well as on body weight management (hypoleptinemia, adrenergic system activation, appetite suppression or serotonin production).…”
mentioning
confidence: 57%
“…Thus, one of the mechanisms triggering inflammation has been associated with adipose tissue hypoxia [4] or increased oxygen tension [5], which affect a number of genes such as HIF-1a, MCP-1, IL-6, GLUT-1, ANGPTL-4 and PPAR-γ [6] that could be involved as a cause or as a consequence reaction to pathologically low or high oxygen conditions. Interestingly, as we hypothesized previously [3] and Kong et al have nicely demonstrated in their article [1], hypoxia is not only an ethological factor or a manifestation of disease, but also a therapeutic tool following different patterns (hypoxic exposure, hypoxic training, intermittent hypoxia under hyperbaric and normobaric conditions), which has been used for pre-acclimation in climbers, or to improve athletes performance as well as for heart, respiratory and nervous system diseases or to regulate body weight [7]. Thus, putative compensatory mechanisms and responses to hypoxia has been described for the respiratory system (hyperventilation, improvement in respiratory function and increase in lung diffusion capacity), in the cardiovascular system (increase in basal heart rate, peripheral vasodilation, normalization of blood pressure or cardiovascular protection), in cellular and metabolic phenomena (angiogenesis, insulin sensitivity enhancement, enzymatic activation or mitochondrial biogenesis), as well as on body weight management (hypoleptinemia, adrenergic system activation, appetite suppression or serotonin production).…”
mentioning
confidence: 57%
“…In this context, intermittent hypoxia may be a tool to manage some obesity-associated risk factors such as cardiovascular disease [32]. Normoxic and hypoxic training have been related to important improvements in specific metabolic risk factors and exercise capacity [50]. Moreover, the stimulus of intermittent normobaric hypoxia, which has been cited as an additive cardioprotective effect, may have relevant clinical implications affecting insulin sensitivity or inflammation [21], while an enhancement of leptin secretion under a hypoxia milieu may also be involved [50].…”
Section: Discussionmentioning
confidence: 99%
“…IHT was found to augment the effects of exercise on obesity. 190 The beneficial effects of adaptation to hypoxia in ischemic cardiac disease have been recognized for many years. 179,180,191 In 1993, Ehrenbourg and Gorbachenkov described favorable effects of IHT on cardiac rhythm disorders in patients with neurocirculatory dysfunction.…”
Section: Iht Reduces Vrfsmentioning
confidence: 99%